Pancreatoduodenectomy without Vascular Resection in Patients with Primary Resectable Adenocarcinoma and Unilateral Venous Contact: A Matched Case Study. (25th November 2018) - Morelli, Luca; Berchiolli, Raffaella; Guadagni, Simone; Palmeri, Matteo; Furbetta, Niccolò; Gianardi, Desirée; Bianchini, Matteo; Funel, Niccola; Caprili, Giovanni; Pollina, Luca Emanuele; Di Candio, Giulio; Mosca, Franco; et al.
Abstract : Purpose . To investigate the oncological outcome and survival of patients following a conservative approach on the portal-mesenteric axis, in an intraoperative ultrasound-selected group of pancreatoduodenectomy (PD), performed on patients with primary resectable with vascular contact (prVC) pancreatic ductal adenocarcinoma (PDAC). Methods . A consecutive series of patients who underwent PD for PDAC at our tertiary care center, between 2008 and 2017, were reviewed. A total of 156 PDs and 88 total pancreatectomies were performed during the study period, including 35 vascular resections. We identified a group of 40 (25.6%) patients with prVC-PDAC in whom after checking the feasibility with intraoperative ultrasound, we were able to perform PD by separation of the tumor from the portomesenteric axis avoiding vascular resection, without residual macroscopic disease (no vascular resection, nvrPD), and compared this group, using case-matched methodology, with the standard PD (sPD) group of primary resectable without vascular contact- (prwVC-) PDAC. Results . The median follow-up was 28.5 ± 23.2 months in the sPD group and 23.8 ± 20.8 months in the nvrPD group (p = 0.35 ). Isolated local recurrence rate was 2/40 (5%) in both groups. Additionally, there were no statistical differences in the systemic progression of the disease (42.5% sPD vs. 45% nvrPD, p = 0.82 ) or local plus synchronous systemic disease rates (2.5% sPD vs. 7.5% nvrPD, p = 0.30 ). The median survival was 22 months for the sPD group and 23 months for the nvrPD group, p = 0.86 . The overall survival was similar in the two groups (1 y: 76.3% sPD vs. 70.0% nvrPD; 3 y: 35.6% vs. 31.6%; and 5 y: 28.5% vs. 25.3%; p = 0.80 ). Conclusion s. PD without vascular resection can be considered safe and oncologically acceptable in selected patients with preoperative diagnosis of prVC-PDAC. The poor prognosis of PDAC is related to the aggressive biology and systemic spread of the tumor, rather than the local control of the disease.